O pensamento Graciliânico e suas relações sociopolíticas e administrativas em Alagoas - Santos, Ângela Maria dos (2019)
This dissertation explore and problematizes some actions and speeches of public administrator Graciliano Ramos de Oliveira (1892-1953) present in the two Reports sent to the governor of the state of Alagoas, Álvaro Paes, in the years 1929-1930, the Code of Conduct implemented by him in his administration as mayor of the city of Palmeira dos Índios AL (August 1928), as well as in the Report of his performance in the Board of Directors of the Public Instruction of Alagoas, from 1933 to 1936. In this sense, the objective of the work is to understand the performances of Graciliano Ramos in his public positions and his political-administrative practices in Alagoas. This, the temporal cut-off covers the decades from 1920 to 1936, when Graciliano Ramos acts with greater prominence in the public sphere. Also included in this work are approaches on modernization and social hygiene, which were instigators of sociocultural transformations in the Brazilian republican period, these factors are objects of analysis and interpretation in all sections of the dissertation under consideration, such as the conception of the new man under the rousseauian and senequian prisms to understand the ideals of education present in the speeches of some literary works of the then director of Public Instruction. For the construction of this master’s work we use as sources the periodicals, works of Graciliano Ramos, newspapers and reports. The documentary corpus of this research was constituted from the analysis of the written reports and published in the local newspapers by the then mayor Graciliano Ramos. Nevertheless, with the prospect of expanding the research, it was necessary to search other collections such as the Public Archive of Alagoas and the Historical and Geographical Institute of Alagoas, also in the National Digital Library and in biographical works.